2015
DOI: 10.1016/j.addbeh.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of residential schooling and of child abuse on substance use problem in Indigenous Peoples

Abstract: Residential schools were the institutions, in operation from the 19th century to the late 20th century, which Indigenous children in Canada were forced to attend. The literature shows that many young people who attended these institutions were victims of neglect and abuse.Negative psychological effects resulting from child abuse have been amply documented.However, very few studies on this subject have been carried out among Canada's Indigenous peoples. The objective of this cross-sectional study is to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 40 publications
3
56
0
1
Order By: Relevance
“…This calculated and devastating program of assimilation amounted to nothing less than "cultural genocide" (Johnston, 2013;MacDonald & Hudson, 2012;TRC, 2015a), and has had a profound, negative impact on generations of Indigenous peoples in Canada (Bombay, Matheson, & Anisman, 2011. Many Indigenous communities in Canada continue to struggle with the intergenerational effects of the IRS system, often manifesting in the form of elevated rates of addiction, violence, suicide and mental illness (Bombay et al, 2011(Bombay et al, , 2014Chandler & Lalonde, 1998;EKOS Research Associates, 2007;Kirmayer, 1994;Ross, Dion, Cantinotti, Collin-Vézina, & Paquette, 2015;Taylor & de la Sablonnière, 2015).…”
Section: Colonization and The Indigenous Peoples Of Canadamentioning
confidence: 99%
“…This calculated and devastating program of assimilation amounted to nothing less than "cultural genocide" (Johnston, 2013;MacDonald & Hudson, 2012;TRC, 2015a), and has had a profound, negative impact on generations of Indigenous peoples in Canada (Bombay, Matheson, & Anisman, 2011. Many Indigenous communities in Canada continue to struggle with the intergenerational effects of the IRS system, often manifesting in the form of elevated rates of addiction, violence, suicide and mental illness (Bombay et al, 2011(Bombay et al, , 2014Chandler & Lalonde, 1998;EKOS Research Associates, 2007;Kirmayer, 1994;Ross, Dion, Cantinotti, Collin-Vézina, & Paquette, 2015;Taylor & de la Sablonnière, 2015).…”
Section: Colonization and The Indigenous Peoples Of Canadamentioning
confidence: 99%
“…The influences and teachings of parents, family and elders are of upmost importance to learning for Indigenous youth and these community members will have to be consulted in the planning of any interventions. 19 Studies among non-indigenous populations have identified approaches to prevention and education that may offer insights for Indigenous communities. For example, the use of protective equipment in hockey including helmets, mouthguards and neckguards 1,34 is not always available for Indigenous youth.…”
Section: Knowledge and Attitudesmentioning
confidence: 99%
“…17 Striking health inequities result from many factors, such as reduced access to medical and rehabilitation services, lack of sport safety equipment 18 and lack of safety education. 19 Only two articles 20,21 were identified in a recent literature review of studies on traumatic brain injury in North American Indigenous populations. 18 These early calls to action for Indigenous brain injury prevention have been unrequited.…”
Section: Introductionmentioning
confidence: 99%
“…20 Therefore, it can be extrapolated that there exists a potential indirect link between poor SES and TBI, with poor SES manifesting as a function of social factors such as increased risk-taking behavior, social dysfunction, and lack of educational resources. 21 For example, approximately 35% of indigenous people in Manitoba live on a reservation. 22 This is just a single Canadian example of the remote physical environment in which some North American indigenous people live.…”
Section: Physical Environmentmentioning
confidence: 99%